PENGARUH TEAMWORK DAN PERILAKU INOVATIF TERHADAP KINERJA PEGAWAI PADA PUSKESMAS PERAK TIMUR KOTA SURABAYA DENGAN KOMPETENSI SEBAGAI VARIABEL MODERASI - Wahyu Hutomo; Anang Kistyanto; Andre Dwijanto Witjaksono (ITB AAS Indonesia Surakarta, 2024)
The performance of employees at optimal health care facilities will improve the quality of health services and the satisfaction of health service users. The purpose of this study was to analyze the effect of teamwork and innovative behavior on performance with competence as a moderating variable. This research was conducted at the Puskesmas Perak Timur, with Judgement sampling obtained a sample of 47 respondents. Statistical data analysis with Structural Equation Modeling (SEM) approach and Partial Least Squares (PLS) technique through SmartPLS software. The results of this study explain, among others, that teamwork has a significant positive effect on employee performance, the more often employees apply teamwork, the higher the performance obtained. Furthermore, innovative behavior has a significant positive effect on employee performance, the more often innovative behavior is implemented, the higher the performance obtained. competence as a moderating variable proved insignificant and played no role in influencing the relationship between teamwork and performance. In addition, competence as a moderating variable proved insignificant and played no role in influencing the relationship between innovative behavior and employee performance. Puskesmas employees consider that not all employees must have competence, all activities can be done in teams and help each other.